The OXTR Single-Nucleotide Polymorphism rs53576 Moderates the Impact of Childhood Maltreatment on Empathy for Social Pain in Female Participants: Evidence for Differential Susceptibility - Flasbeck, Vera; Moser, Dirk; Kumsta, Robert; Brüne, Martin (Frontiers in Psychiatry, 2018)
Previous research has associated genetic variations of the oxytocin receptor with individual differences in human social behavior. Specifically, homozygous carriers of the G-allele of the single nucleotide polymorphism rs53576 have been reported to display more trust, empathy and prosocial behavior and were less sensitive towards stress and maltreatment during childhood when compared to A-allele carriers. With regard to Borderline Personality Disorder (BPD), a psychiatric condition that is often associated with the experience of childhood adversity, it has been suggested that A-allele carriers are more vulnerable to developing psychopathological signs and symptoms. In the present study we investigated whether childhood trauma, as assessed by the Childhood Trauma Questionnaire (CTQ), affects empathy for somatic and psychological pain, and how this is moderated by genotype, in a sample of 302 individuals (148 of whom were diagnosed with BPD). We found a three-way interaction between genotype, group and pain condition. Posthoc comparisons revealed that patients with BPD carrying at least one A-allele, rated psychological pain as more intense compared to controls, whereas no difference between groups emerged in GG homozygotes. Moreover, a moderating effect of genotype appeared on the impact of childhood trauma on empathy for psychological pain. In addition, a positive correlation of CTQ scores and empathy appeared only in A-allele carriers (GA + AA), independent of diagnosis. Together, A-allele carriers, especially those with BPD, seemed to be responsive to the impact of adversity on empathy-for-pain, while GG homozygotes were not, which is compatible with the idea of differential susceptibility.